Patient-Completed Caprini Risk Score for Venous Thromboembolism Risk Assessment: Developed and Validated from 1,017 Medical and Surgical Patients - Zhang, Zhu; Wu, Yifan; Liu, Qingxia; Dong, Fen; Pang, Wenyi; Zhe, Kaiyuan; Wan, Jun; Xie, Wanmu; Wang, Wei; Yang, Peiran; Sun, Aihua; Zhai, Zhenguo (TH Open, 2022)
Background The Caprini Risk Score (CRS) is one of the most widely used risk assessment models for venous thromboembolism (VTE). A well-validated patient-completed CRS form may allow patients to self-report and simplify the evaluation by health care workers.Methods The Chinese version of the CRS was optimized for easy understanding in a pilot study. The amended CRS form was completed by prospectively recruited patients and blinded nurses. The agreement levels of the individual questions and the total scores of patient and nurse-completed forms were compared using the Kappa value. The total scores were used for risk stratification of patients. Correlation and differences between patient and nurse-completed forms were analyzed using the Spearman correlation and Bland–Altman method, respectively.Results We recruited 504 medical patients and 513 surgical patients, aged 52.7 ± 16.3 years, of which 443 (43.6%) were men, and 91.6% of the patients were educated beyond junior high school. The patients spent less time to complete the form compared with trained nurses. There was good question-to-question agreement between patient and nurse-completed CRS (k >0.6 for most questions, p < 0.0001). The total scores also showed good agreement (k = 0.6097, p < 0.0001), and enabled the classification of patients into different risk groups. The patient and nurse-derived scores were highly correlated (Spearman's r = 0.84), and without extreme values (p < 0.0001).Conclusion We have created and verified a Chinese version of the patient-completed CRS, which showed good agreement and correlation with nurse-completed CRS. CRS represents a suitable tool for VTE risk assessment of hospitalized patients in China.
Keywords: venous thromboembolism; risk assessment; Caprini; self-report; validation